2015
DOI: 10.1038/npp.2015.356
|View full text |Cite
|
Sign up to set email alerts
|

Double Dissociation of Monoacylglycerol Lipase Inhibition and CB1 Antagonism in the Central Amygdala, Basolateral Amygdala, and the Interoceptive Insular Cortex on the Affective Properties of Acute Naloxone-Precipitated Morphine Withdrawal in Rats

Abstract: Both CB 1 receptor antagonism and agonism, in particular by 2-arachidonyl glycerol (2-AG), have been shown to reduce somatic symptoms of morphine withdrawal (MWD). Here we evaluated the effects of both systemic pretreatment with the monoacylglycerol lipase (MAGL) inhibitor MJN110 (which selectively elevates 2-AG) and central administration of both MJN110 and the CB 1 antagonist (AM251) on the affective properties of MWD. Acute MWD induced place aversion occurs when naloxone is administered 24 h following a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…To date, there are no reports assessing i.c.v. administration of MJN110, although several studies have demonstrated CB 1 receptor‐dependent effects of localized injection (2 μg) into distinct brain regions (Limebeer et al ., ; Sticht et al ., ; Wills et al ., ). As the current study assessed i.c.v.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are no reports assessing i.c.v. administration of MJN110, although several studies have demonstrated CB 1 receptor‐dependent effects of localized injection (2 μg) into distinct brain regions (Limebeer et al ., ; Sticht et al ., ; Wills et al ., ). As the current study assessed i.c.v.…”
Section: Methodsmentioning
confidence: 99%
“…The anxiety-like behavior observed during protracted withdrawal is alleviated by lesions of the medial IC. The cannabinoid system has also been implicated, with the inhibition of monoacylglycerol lipase (causing elevation of the endocannabinoid 2-arachidonyl glycerol; 2-AG) in the pGIC preventing the acquisition of CPA from morphine withdrawal, which was reversed by the blockade of cannabinoid-1 receptors (Wills et al, 2016).…”
Section: Preclinical Evidence For the Insulamentioning
confidence: 99%
“…Contrary to somatic withdrawal, the cannabinoid agonist, Δ 9 THC, and the FAAH enzyme inhibitors, PF3845 and URB-597, tested were unable to modify the establishment of a naloxone-precipitated CPA ( Wills et al, 2014 ; Gamage et al, 2015 ). However, while activation of the cannabinoid system via exogenous cannabinoid administration or endogenous elevation of AEA proved to have little efficacy, inhibition of MAGL activity and concomitant elevation of 2-AG showed mixed ( Wills et al, 2014 , 2016 ; Gamage et al, 2015 ) but more promising results. Given that these discrepant findings were obtained by different laboratories using different procedures, compounds (JZL-184 vs. MJN110), and species (mice vs. rats), more research into the potential of MAGL inhibition in reducing affective opioid withdrawal will be required in order to elucidate its role.…”
Section: Cannabinoids On Opiate Withdrawalmentioning
confidence: 99%
“…Although the deleterious reputation of cannabinoid antagonists/inverse agonists may limit their therapeutic potential ( Bergman et al, 2008 ), blockade of the endocannabinoid system may be effective for reducing affective opioid withdrawal. Indeed, acute CB 1 R antagonism (with both AM251, and the neutral CB 1 antagonists, AM4113, and AM6527) was effective in preventing the establishment of a naloxone-precipitated CPA ( Wills et al, 2014 , 2016 ). This is in contrast to the ability of acute CB 1 antagonism to reliably reduce somatic withdrawal, but could be attributed to the fact that the CPA paradigm may provide a more sensitive measure of opioid withdrawal ( Azar et al, 2003 ).…”
Section: Cannabinoids On Opiate Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation